Worldview for Christian witness - Kraft, Charles H. (William Carey Library, 2008)
Charles Kraft invites readers to understand reality as God sees it by learning to take seriously the insights of other societies. The diversity of cultures can seem obvious, but to really understand the significance of those surface level differences, one needs to understand the deep level assumptions on which they are based. - Publisher.